Non-Canonical Effects of ACTH: Insights Into Adrenal Insufficiency - Hasenmajer, Valeria; Bonaventura, Ilaria; Minnetti, Marianna; Sada, Valentina; Sbardella, Emilia; Isidori, Andrea M. (Frontiers in Endocrinology, 2021)
Introduction Adrenocorticotropic hormone (ACTH) is produced from proopiomelanocortin, which is predominantly synthetized in the corticotroph and melanotroph cells of the anterior and intermediate lobes of the pituitary gland and the arcuate nucleus of the hypothalamus. Although ACTH clearly has an effect on adrenal homeostasis and maintenance of steroid hormone production, it also has extra-adrenal effects that require further elucidation. Methods We comprehensively reviewed English language articles, regardless of whether they reported the presence or absence of adrenal and extra-adrenal ACTH effects. Results In the present review, we provide an overview on the current knowledge on adrenal and extra-adrenal effects of ACTH. In the section on adrenal ACTH effects, we focused on corticosteroid rhythmicity and effects on steroidogenesis, mineralocorticoids and adrenal growth. In the section on extra-adrenal effects, we have analyzed the effects of ACTH on the osteoarticular and reproductive systems, adipocytes, immune system, brain and skin. Finally, we focused on adrenal insufficiency. Conclusions The role of ACTH in maintaining the function of the hypothalamic–pituitary–adrenal axis is well known. Conversely, if we broaden our vision and analyze its role as a potential treatment strategy in other conditions, it will be evident in the literature that researchers seem to have abandoned this aspect in studies conducted several years ago. We believe it is worth re-evaluating the role of ACTH considering its noncanonical effects on the adrenal gland itself and on extra-adrenal organs and tissues; however, this would not have been possible without the recent advances in the pertinent technologies.